2009
DOI: 10.1309/ajcpe0l7cijzbifr
|View full text |Cite
|
Sign up to set email alerts
|

A bcr3/Short Form PML-RARα Transcript in an Acute Promyelocytic Leukemia Resulted From a Derivative Chromosome 17 Due to Submicroscopic Insertion of the PML Gene Into the RARα Locus

Abstract: Acute promyelocytic leukemia (APL) is a subtype of acute myeloid leukemia. Submicroscopic insertion of RARα into PML, resulting in PML-RARα from derivative chromosome 15, has been rarely reported. Herein, we describe a functional PML-RARα transcript from the long arm of derivative chromosome 17 in a patient with microgranular APL. The conventional karyotype showed normal chromosomes 15 and 17. It is interesting that interphase and metaphase fluorescence in situ hybridizations demonstrated a fusion signal on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, bcr3 patients with early death within less than a month of diagnosis did not even complete or receive the treatment and others who developed ATRA syndrome are still in event free survival suggesting that bcr3 isoform expression at diagnosis may have a direct role in the patient outcome. It is possible that the mechanism in which bcr3 isoform is generated such as from a derivative chromosome 17 due to submicroscopic insertion of the PML gene into RARα locus [ins ( Tallman et al, 2002 )(17;15)] as reported in one case ( Wang et al, 2009 ). In a transgenic mouse model, bcr3 isoform significantly increased the penetrance of APL in mice expressing Pml-Rarα suggesting its role in leukemogenesis ( Pollock et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, bcr3 patients with early death within less than a month of diagnosis did not even complete or receive the treatment and others who developed ATRA syndrome are still in event free survival suggesting that bcr3 isoform expression at diagnosis may have a direct role in the patient outcome. It is possible that the mechanism in which bcr3 isoform is generated such as from a derivative chromosome 17 due to submicroscopic insertion of the PML gene into RARα locus [ins ( Tallman et al, 2002 )(17;15)] as reported in one case ( Wang et al, 2009 ). In a transgenic mouse model, bcr3 isoform significantly increased the penetrance of APL in mice expressing Pml-Rarα suggesting its role in leukemogenesis ( Pollock et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, these cases show variant translocations involving RARA with other partner genes including PLZF, NPM, NUMA, STAT5B, ZBTB16, PRKAR1A, FIP1L1, and BCOR. These cases are referred to as APL with variant RARA translocations and are often unresponsive to ATRA [1,4].…”
Section: Introductionmentioning
confidence: 99%